Description Of Providing Drug Information To Myalgia Patients At The Waru Pamekasan Community Health Center, East Java - Ida Karmila Wati; Naili Usawatun Hasanah; Ach. Faruk Alrosyid (Penerbit Hellow Pustaka, 2024)
Providing Information Services are activities carried out by pharmacists in providing information regarding drug information that is impartial, critically evaluated and with the best evidence in all aspects of drug use to other professions, patients or the public. Puskesmas is a health service facility that carries out public health efforts and first-level individual health efforts, by prioritizing promotive and preventive efforts, to achieve the highest level of public health in its working area. The aim of this research is to determine the implementation of drug information services with pharmaceutical service standards at the Waru Community Health Center.This type of research is descriptive research. The sample in this study was myalgia patients at the Waru Pamekasan Community Health Center who met the inclusion and exclusion criteria. The samples in this study amounted to 43 samples. The sampling technique uses purposive sampling. The method for collecting data is using a data checklist filled in by researchers according to the results of observations.The research results showed that the Drug Information service for myalgia patients at the Waru. in assessing drug name information (100%), drug preparation information (53,4%), dosage information (34,8%), information on how to use the drug (100%), drug storage information (0%), drug indication information (100%), information on drug contraindications (69,7%), information on drug stability (0%), information on drug side effects (10%), information on drug interactions (0%).